Earlobe Inflammation from a Palm Thorn Injury - Press, Yan (Am J Trop Med Hyg, 2016)
Injury from the thorn of a palm tree is characterized by a prolonged, painful inflammatory reaction. Even when the source of the inflammation is diagnosed, appropriate treatment is usually delayed because family doctors are not familiar with the entity. Penetration of a palm thorn into the earlobe is an unrecognized cause of local inflammation. We describe a case of injury from a palm tree thorn in this uncommon site. We present the technique of transillumination for the identification and removal of the palm thorn.